NATURAL LANGUAGE PROCESSING WITH PROLOG - Dwi Wahjoeningratri Dyah Indriani; Dra Ida Ayu Wiastiti, Mkom (Jurnal Sistem Informasi, 1997)
Each user, wherever located, wants the creation of communication between humans and computers without difficulty in the field of language. So desirable an application program that has the ability to detect everyday discuss and understand if there is a grammatical error free contexts using Parser. First sentence that is input will be identified compilation of words, matched to the one in the dictionary database by type of data, then the order of those words will be matched according to type phrases with objects and phrases pattern of work that has been determined. As the final sentence of the program will be visible signs of 'true' (for the correct sentence).